Karakteristik Fisik Ayam Broiler yang Diberi Pakan Tambahan Jerami Bawang Merah - Dyah Nurul Afiyah; Supriyono Supriyono; Riska Nurtantyo Sarbini (Musamus Journal of Livestock Science, 2021)
Red onions hay are one ingredient that can be used again because huge amount and high nutrition. The purpose of this study is to find physical characteristic of broiler chicken fed with red onion hay. The result of this research indicates that the addition of red onion hay on 0% , 3% , 6% and 9% can give insignificant effect to the carcasses percentage, the meat percentage, water holding capacity and cooking loss.